ANALISIS FRAMING ENTMAN PADA TEKS EDITORIAL “KABAR BURUK SETELAH SOEHARTO JADI PAHLAWAN”: STUDI KASUS PADA MEDIA ONLINE TEMPO.CO - Hanina Afifah; Zahra Zaina Rusty (ADISAM PUBLISHER, 2025)
This study analyzes the framing of Tempo’s editorial entitled “Kabar Buruk Setelah Soeharto Jadi Pahlawan” published on November 12, 2025, which responds to the Indonesian government’s decision to grant former president Soeharto the title of National Hero. The appointment sparked public controversy due to Soeharto’s historical association with authoritarian rule and alleged gross human rights violations. This research aims to examine how Tempo constructs meaning and articulates its institutional stance through editorial framing. Employing a qualitative descriptive approach, the study uses Robert N. Entman’s framing model, which consists of problem definition, causal interpretation, moral evaluation, and treatment recommendation. The findings reveal that Tempo frames the decision as a political and moral setback that threatens the spirit of reform and historical justice. The government is positioned as the primary actor responsible for selectively interpreting history while neglecting unresolved human rights abuses. Moral judgment emerges as the dominant framing element, emphasizing the suffering of victims and the ethical implications of state-sanctioned symbolic recognition. The editorial implicitly recommends maintaining critical historical memory and resisting the normalization of authoritarian figures. This study demonstrates that editorial framing functions as a strategic discursive tool through which media shape public interpretation, contest state narratives, and contribute to debates on political memory and human rights